Residual Effects of Biosolids Application on Forage Production of Semiarid Grassland in Jalisco, Mexico - Pedro Jurado-Guerra; Miguel Luna-Luna; Ernesto Flores-Ancira; Ruben Saucedo-Teran (Applied and Environmental Soil Science)
Single application of biosolids increases forage production on semiarid grasslands. Residual effects of biosolids on forage production have been scarcely measured in semiarid grasslands. The objective was to evaluate the residual effects of biosolids application on forage production of blue grama (Bouteloua gracilis (Willd. ex Kunth) Lag. ex Griffiths) and other grasses at a semiarid grassland in Jalisco, Mexico. The study was performed at shortgrass prairie in northeast Jalisco. Field plots were selected to include blue grama plants before rainy season in 2002. Aerobic biosolids were applied at 0 (control), 15, 30, 45, 60, 75, or 90 dry Mg ha−1 under a completely random design with five replications. Forage production was estimated by clipping at the end of the growing season during five years. Data analysis was performed with linear mixed model and repeated measures. Forage production was influenced by a rate × year × species interaction (P=0.0001). Blue grama forage production increased with increasing biosolids rates during all years, with the magnitude of this response varying among years. Forage production of other grass species slightly decreased with biosolids application. Single biosolids application had a residual effect on forage production throughout five years in semiarid grasslands.